Model of formation and development of intellectual teams - Kalyta, N. I.; Ponomarova, S. V. (My University, 2017)
The work is devoted to the task of intellectual team’s management, namely the problem of their formation, adaptation and training. The paper presents a mathematical model of the multifactor estimation of intellectual team, allowing to choose the best of its composition from a plurality of possible options. To formalize the problem using utility theory, candidates in the team are assessed for their professional, profile and personality characteristics. The model also takes into account the requirements for the competence of the performers. Various options for the formation of the optimality criteria are considered. The paper also considers the process of motivating the members of the intellectual team for their development, namely, adaptation and training.
Keywords: theory of utility; attractiveness of the applicant; adaptation; training; motivating the members of the intellectual team